Pola Makan Mengandung Kadar Lemak Jenuh dan Kolesterol Tinggi Mengakibatkan Peningkatan Tekanan Darah dan Stroke pada Penderita Hypertensi di Puskesmas Padang Tahun 2023 - Eka Seba Marta (Sekolah Tinggi Ilmu Kesehatan YPAK Padang, 2023)
The prevalence of hypertension in West Sumatra is around 22.6%, in Padang City in 2021 it will be 51.36%. Based on data from the community health center in Padang City, hypertension in the Alai Community Health Center was 63.1%. The aim of the research was to determine the eating patterns that result in increased blood pressure and stroke in hypertension sufferers at the Padang Community Health Center in 2023. This type of research is analytical with a cross sectional design. The population is hypertension sufferers. The population is 309 respondents. Accidental sampling technique totaling 76 people. Chi-square analysis CI 64.5% (α = 0.00). The research was conducted on February 12 – August 20 2023 Keywords: Diet; Blood Pressure; Stroke; Hypertension